Vitamin D in the Life of the Athlete: A Narrative Review of Biology, Status, Performance, Injury and Practical Management - Poręba, Martyna; Poręba, Kacper; Prokopczyk, Kamila; Rusiłowicz, Rafał; Matuszewska, Julia; Peszt, Michał Józef; Wasilczuk, Antoni; Lewandowska-Mackiewicz, Aleksandra; Szaryński, Mikołaj; Jakubowska, Paulina (Quality in Sport, 2025)
Introduction Vitamin D is essential for bone health and supports muscle and immune function. Deficiency is common among athletes due to indoor training, high latitudes, winter, clothing and darker skin. The main concern is how vitamin D status and supplementation affect performance, recovery and risk of illness or injury. Aim This review summarizes evidence on: • mechanisms linked to muscle and immune function, • prevalence and causes of deficiency, • impact on strength, endurance and recovery, • role in bone health, fractures and soft tissue injuries, • associations with respiratory infections, • strategies for screening and supplementation. Material and Methods A narrative review was conducted using PubMed and Google Scholar. Priority was given to randomized controlled trials, systematic reviews, meta-analyses and clinical guidelines. Results Vitamin D receptor activity regulates calcium handling, mitochondrial function and tissue repair. Deficiency affects 40–70% of athletes in winter, particularly those engaged in indoor and high-latitude sports. Supplementation effectively raises serum 25(OH)D levels. Effects on performance are modest but more pronounced when deficiency is corrected. Calcium combined with vitamin D reduces stress fracture risk in military cohorts. Observational studies indicate that low vitamin D increases the risk of bone stress injuries. Evidence for protection against respiratory infections is inconclusive. Conclusions Adequate vitamin D supports bone integrity and recovery. Ergogenic effects are modest and mainly relevant in deficiency. Guidelines recommend individualized vitamin D₃ supplementation, usually 1,000–2,000 IU/day, and screening for high-risk athletes. High-dose bolus regimens are not recommended. Maintaining sufficiency reduces bone injury risk and supports overall health, though performance benefits in sufficient athletes remain uncertain.